No king without a crown – impact of the nanomaterial-protein corona on nanobiomedicine. (February 2015) - Docter, Dominic; Strieth, Sebastian; Westmeier, Dana; Hayden, Oliver; Gao, Mingyuan; Knauer, Shirley K; Stauber, Roland H
Besides the wide use of nanomaterials in technical products, their application spectrum in biotechnology and biomedicine is steadily increasing. Whereas the physico-chemical properties and behavior of nanomaterials can be engineered and characterized accurately under idealized conditions, this is no longer the case in complex physiological environments. In biological fluids, proteins rapidly bind to nanomaterials forming the protein corona, critically affecting the nanomaterials' biological identity. As the corona impacts in vitro and/or in vivo nanomaterial applications, we here review the concept of the protein corona and its analytical dissection. We comment on how corona signatures may be linked to effects at the nano–bio interface and conclude how such knowledge is offering novel opportunities for improved nanomedicine.